Hypothesis of K+-Recycling Defect Is Not a Primary Deafness Mechanism for Cx26 (GJB2) Deficiency - Zhao, Hong-Bo (Frontiers in Molecular Neuroscience, 2017)
K+-recycling defect is a long-standing hypothesis for deafness mechanism of Connexin26 (Cx26, GJB2) mutations, which cause the most common hereditary deafness and are responsible for >50% of nonsyndromic hearing loss. The hypothesis states that Cx26 deficiency may disrupt inner ear gap junctions and compromise sinking and recycling of expelled K+ ions after hair cell excitation, causing accumulation of K+-ions in the extracellular space around hair cells producing K+-toxicity, which eventually induces hair cell degeneration and hearing loss. However, this hypothesis has never been directly evidenced, even though it has been widely referred to. Recently, more and more experiments demonstrate that this hypothesis may not be a deafness mechanism underlying Cx26 deficiency. In this review article, we summarized recent advances on the K+-recycling and mechanisms underlying Cx26 deficiency induced hearing loss. The mechanisms underlying K+-sinking, which is the first step for K+-recycling in the cochlea, and Cx26 deficiency induced cochlear developmental disorders, which are responsible for Cx26 deficiency induced congenital deafness and associated with disruption of permeability of inner ear gap junctional channels to miRNAs, are also summarized and discussed.